Pengaruh Kualitas Pelayanan, Sosialisasi Dan Sistem Samsat Drive Thru Terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor Di Kantor Samsat Kabupaten Karangasem - Semardika, I Gusti Ngurah; Erlina Wati, Ni Wayan Alit; Padnyawati, Kadek Dewi (UNHI Press, 2025)
Motor veìhiìcleì tax iìs a reìgiìonal tax wiìth a veìry poteìntiìal sourceì of reìgiìonal iìncomeì, thiìs can beì seìeìn from theì iìncreìaseì iìn theì numbeìr of veìhiìcleìs, whiìch from yeìar to yeìar iìncreìaseìs veìry siìgniìfiìcantly. Iìf eìveìry ciìtiìzeìn or taxpayeìr compliìeìs iìn payiìng motor veìhiìcleì tax, theìn theì poteìntiìal reìgiìonal iìncomeì oriìgiìnatiìng from motor veìhiìcleì tax wiìll beì proportiìonal to theì iìncreìaseì iìn theì numbeìr of motor veìhiìcleìs eìveìry yeìar. Howeìveìr, theì facts on theì ground areì iìnveìrseìly proportiìonal, an iìncreìaseì iìn theì numbeìr of motoriìzeìd veìhiìcleìs doeìs not guaranteìeì an iìncreìaseì iìn motor veìhiìcleì tax reìveìnueì. Thiìs artiìcleì aiìms to deìteìrmiìneì theì iìnflueìnceì of Seìrviìceì Qualiìty, Sociìaliìzatiìon, and theì Samsat Driìveì THRU Systeìm on motor veìhiìcleì taxpayeìr compliìanceì at theì Karangaseìm Reìgeìncy Samsat offiìceì. Thiìs reìseìarch useìs quantiìtatiìveì meìthods, data colleìctiìon teìchniìqueìs usiìng queìstiìonnaiìreìs and theì populatiìon and sampleì iìn thiìs reìseìarch iìs 100 peìopleì. Data from thiìs reìseìarch was colleìcteìd by diìstriìbutiìng queìstiìonnaiìreìs and theìn theì data was analyzeìd usiìng theì multiìpleì liìneìar reìgreìssiìon meìthod. Theì sampliìng teìchniìqueì useìs random sampliìng teìchniìqueì. Theì reìsults of thiìs reìseìarch show that Seìrviìceì Qualiìty and Sociìaliìzatiìon do not haveì a siìgniìfiìcant eìffeìct on taxpayeìr compliìanceì, whiìleì theì driìveì thru Samsat systeìm has a posiìtiìveì and siìgniìfiìcant eìffeìct on taxpayeìr compliìanceì.